Pengaruh Kualitas Layanan Terhadap Kepuasan Wali Murid di Lembaga Bimbingan dan Motivasi Belajar (BMB) Air-LANGGA Ponorogo - Chelonia, Zioravinky; Rosyanafi, Rofik Jalal (J+PLUS UNESA, 2024)
Service quality has a major role in shaping customer perceptions of an institution. Providing quality services is one of the strategies carried out by educational institutions to increase student satisfaction. The aim of this research is to determine the effect of service quality on the satisfaction of parents at the Air-LANGGA Ponorogo Learning Guidance and Motivation Institute. This research uses a quantitative approach with associative methods. The population in this study was 75 parents with a sample size of 43 parents. The data collection techniques used in this research were questionnaires, documentation and observation. Through the Product Moment correlation test, a significance value of 0.000 was obtained, where this value is smaller than 0.05. The correlation coefficient value obtained was 0.664. If adjusted to the r value interpretation table, it is classified in the strong category. So it can be concluded that service quality has a significant positive influence on the satisfaction of parents at the Air-LANGGA Ponorogo Learning Guidance and Motivation Institute (BMB).